PERBEDAAN PENGGUNAAN METODE DEMONSTRASI DENGAN METODE CERAMAH TERHADAP HASIL BELAJAR SISWA PADA MATERI ALAT INDRA MANUSIA DI KELAS IV SDN 13 CINGKARIANG KABUPATEN AGAM - Wulandari, Hastin; Zuryanty, Zuryanty; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research was toknowing difference between the use of demonstration methods with lecture methods on student learning outcomes on the material of human senses in class IV SD Negeri 13 Cingkariang. This research is a quantitative research with experimental research type, and quasy experimental research design. Sampling data was coleccetd by Total Sampling technique. The sample of this study amounted to 42 people with a population 42 people. The instrument that used to ccollecting data  is objective test with multiple choice item. The results is tcount> ttabel, 3.4927> 2.021 withα = 0.05 which means H0is rejected. The average posttest result in the experiment class is 83.80 and the control class is 75.23. So Ha accepted that there is a significant difference that the use of demonstration method is better than the lecture method on the students' science learning outcomes on the material of the human in class IV SD Negeri 13 Cingkariang. Keywords: Demonstration Method, Learning Outcomes, Human Senses